Long-Term Development of Embryonic Cerebellar Grafts in Two Strains of Lurcher Mice - Cendelin, Jan; Purkartova, Zdenka; Kubik, Jakub; Ulbricht, Erik; Tichanek, Filip; Kolinko, Yaroslav (Cerebellum (London, England), 2018)
For many degenerative cerebellar diseases, currently, no effective treatment that would substantially restore cerebellar functions is available. Neurotransplantation could be a promising therapy for such cases. Nevertheless, there are still severe limitations for routine clinical use. The aim of the work was to assess volume and morphology and functional impact on motor skills of an embryonic cerebellar graft injected in the form of cell suspension in Lurcher mutant and wild-type mice of the B6CBA and C3H strains after a 6-month survival period. The grafts survived in the majority of the mice. In both B6CBA and C3H Lurcher mice, most of the grafts were strictly delimited with no tendency to invade the host cerebellum, while in wild-type mice, graft-derived Purkinje cells colonized the host's cerebellum. In C3H Lurcher mice, but not in B6CBA Lurchers, the grafts had smaller volume than in their wild-type counterparts. C3H wild-type mice had significantly larger grafts than B6CBA wild-type mice. No positive effect of the transplantation on performance in the rotarod test was observed. The findings suggest that the niche of the Lurcher mutant cerebellum has a negative impact on integration of grafted cells. This factor seems to be limiting for specific functional effects of the transplantation therapy in this mouse model of cerebellar degeneration.
Keywords: metoda rotující tyčky; modely nemocí na zvířatech; druhová specificita; Mice, Inbred CBA; Transplantation; Male; Graft Survival; longitudinální studie; Mice, Neurologic Mutants; Mice, Inbred C3H; Rotarod Performance Test; Lurcher mouse; Neurodegenerative Diseases; nemoci mozečku; transplantace mozkové tkáně; mužské pohlaví; Motor Skills; myši - mutanty neurologické; myši inbrední C3H; Species Specificity; Brain Tissue Transplantation; Cerebellar Diseases; Cerebellum; neurodegenerativní nemoci; zelené fluorescenční proteiny; Animals; Cerebellar degeneration; ženské pohlaví; myši transgenní; zvířata; přežívání štěpu; Disease Models, Animal; Green Fluorescent Proteins; mozeček; Longitudinal Studies; motorické dovednosti; Female; Purkinje cell; myši inbrední CBA; Mice, Transgenic